Small Business – Forgotten and in need of protection from unfairness? - Freilich, A.; Webb, Eileen (University of Western Australia, 2013)
In light of the statutory protections that have been introduced and developed for the benefit of consumers in their contracts with commercial entities, the vulnerable position of small business in their contracts with bigger business has become even more apparent. Given the diverse nature of small businesses and the fact that small businesspeople share many characteristics with consumers, it is artificial for two individuals to suffer the same wrong but that only one is entitled to recourse. Such denial disregards the inequity of the conduct and focuses instead on a rather perfunctory classification. This article considers why the UCT provisions in the ACL should be extended to small businesses. In the likelihood that such amendments will not be forthcoming, the article considers common law and statutory alternatives for small businesses faced with unfair contract terms. First, it is suggested that common law doctrines and rules may need to be revisited and rethought so they can provide some assistance to small business, so that in their contracts they are not left entirely to the mercy of larger players. Second, the article considers whether the unconscionability provisions in the ACL may be used to provide some relief for small businesses impacted upon by unfair contract terms.